Theoretical foundations of modernization for the sustainable development of Russian regions ("Journal "U". Economy. Management. Finance.", 2023)
The most important role for the development of Russian regions is stable and sustainable modernization. Modernization is a key moment in the socio-economic development of not only the region but the country in the macroeconomic global aspect. The process includes the creation of innovative solutions, strengthening the formation of socio-economic potential and the introduction of new technologies itself.The concept of "economic knowledge" should be considered a theoretical aspect of modernization of mono. Priority in this concept is given to the development of economic sciences and their practical orientation and adaptation to modern realities. The article considers modernization as a multifaceted phenomenon that affects not only the economic and industrial sphere of society, but also the political and cultural, as well as a comprehensive opinion about the process under consideration, which has, in addition to positive, negative aspects concerning the cultural sphere of society. The research conducted by modern scientists contributes to the creation of a new innovative environment, which should subsequently lead to an increase in the level of competitiveness of Russian regions, both in domestic and foreign markets.
Keywords: Modernization; development; region; implementation; infrastructure; economy; stability; competitiveness; globalization; social sphere; production; innovation